Inductively Coupled Plasma Reactive Ion Etching of Magnetic Tunnel Junction Stacks in a CH3COOH/Ar Gas. (1st January 2015) - Garay, Adrian Adalberto; Choi, Ji Hyun; Hwang, Su Min; Chung, Chee Won
Abstract : The etch characteristics of hard masked MTJ (Magnetic Tunnel Junctions) stacks were investigated using inductively coupled plasma reactive ion etching in a CH3 COOH/Ar gas mixture as a function of gas mixture concentration and etch time. A high degree of anisotropy in the etch profile and fast etch rates were achieved when the MTJ stacks were etched in the CH3 COOH/Ar gas mixture. When etched in 25% CH3 COOH for 3 min, a stack: space ratio of 1:1 was obtained and EDS analysis showed no significant redeposition along the sidewall. A high degree of anisotropy was accomplished without redepositions or etch residues.